Sipepeg Application: Social Service Innovation in Optimizing Social Welfare Services - Awaludin, Jeni; Reinaldi, Muhamad Fariz; Permana, Ipik (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the SIPEPEG application, an innovation by the Cirebon Regency Social Service aimed at improving public services for Social Welfare Service Providers (PPKS). Using a qualitative approach with interviews, observation, and documentation, the study evaluates the innovation based on Everett M. Rogers’ five characteristics of innovation: relative advantage, compatibility, complexity, trialability, and observability. The findings indicate that SIPEPEG has significantly improved administrative processes for the PPKS community through PUSKESOS officers. However, challenges remain, particularly in the complexity dimension, such as limited operating hours and access issues for those without mobile devices. The study recommends strengthening human resources, enhancing collaboration among bureaucratic partners, and increasing commitment to improve the effectiveness and quality of SIPEPEG services.